REDUPLIKASI BAHASA MELAYU RIAU DIALEK ROKAN HILIR - Dina Auliya; Hasnah Faizah AR; Charlina Charlina (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstact: this study discusses the Riau Malay language dialects reduplication Rokan Downtream . this research study in morfologis menfenai reduplicated forms and meaning contained in the malay language Riau dialect Rokan downstream. This study used a qualitative approach and descriptive method that aims to describe the form and meaning of Riau Malay language dialct reduplication Rokan Downstream.Keywords : Riau Malay language, dialects reduplication, downstream rokan hilir.